Impact of interest rates fluctuations on the financial performance of companies infinancial sector of sri lanka - Uthayakumar, R.; Jayawardhane, W.S.; Mudiyanselage, W. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
The objective of this study was to examine the impact of interest rates fluctuations on the financial performance of companies in financial sector in Sri Lanka. The study was conducted among sixty five listed companies representing banking, insurance and finance industries with a reference period of past forty quarters of the years ranging from 2008 to 2017. Average Weighted Deposit Rate,Average Weighted Lending Rate, Sri Lanka Inter Bank Offer Rate, and Treasury Bill Rate were assumed as independent variables and the financial performance of companies was assumed as dependent variable in the model of the study. All the above interest rates were obtained from Central Bank records for the above forty quarters. The financial performance of the companies was measured with industrial averaged ratios of Return on Assets and Return on Equity for the above corresponding reference period. The Pearson Correlation and multiple regression analyses were applied using latest version of the Statistical Package for Social Sciences to find any significant linear and functional relationship between the assumed independent and dependent variables. The output of the correlation analysis indicated that a statistically significant positive relationship exists between three types of interest rates (Average Weighted Lending Rate, Sri Lanka Interbank Offer Rate, and Treasury Bill Rate) and the indicators of financial performance (Return on Assets and Return on Equity) with the positive correlation coefficients of 0.439, 0.491, 0.619, 0.581, 0.513, and 0.581 respectively. The results of multiple regression analysis revealed a significant impact of interest rate fluctuations on financial performance with the coefficients of determination (R Square) of 0.455 with Return on Assets, and 0.477 with Return on Equity. Hence, it was concluded that the interest rates fluctuations related to the Average Weighted Deposit Rate and the Average Weighted Lending Rate are recognized as the factors having significant influence on determining the financial performance of companies as measured by the Return Equity in the financial sector consisting of banking, financing, and insurance industries in Sri Lankawhile the major portion of variations in their financial performance might be explained by other non-interests related factors.
Keywords: Return on Assets; Return on Equity; Average Weighted Lending Rate; Sri Lanka Interbank Offer Rate; Treasury Bill Rate